Kinetic modeling and optimization of operating parameters for transvinylation of lauric acid - Kamble, Sanjay P.; Manjarekar, Onkar; Mawale, Ravi; Kulkarni, Bhaskar D.; Chowdary, Naresh; Gupte, Milind Y.; Barve, Prashant P. (International Journal of Chemical Kinetics, 2012)
The transition metal complex catalyzed transvinylation of carboxylic acid with vinyl acetate monomer is of significant interest to industry. The palladium complex catalyzed transvinylation of lauric acid using vinyl acetate monomer is a reversible reaction. In present article, design of experiments (DOE) statistics is used to study effects of various operating parameters on transvinylation of lauric acid. The kinetic parameters forward and backward rate constants and the thermodynamic parameters such as equilibrium constant and energy of activation of the transvinylation of lauric acid were estimated using the Dynochem model. The optimum operating parameters for the transvinylation of lauric acid were then predicted using the Dynochem model and verified by performing the actual experiments to validate the model. It was found that the experimental results match with the predicted one. (c) 2012 Wiley Periodicals, Inc. Int J Chem Kinet 44: 624634, 2012

Kinetic studies on an algal biofilm reactor for raw sewage water treatment - Gera, Gayatri S.; Yewalkar, Swati N.; Nene, Sanjay; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Chemical Engineering & Technology, 2016)
A packed-bed algae biofilm reactor was developed using porous and nonporous dual packings. The biofilm was cultivated on reticulated polyurethane foam cubes. The nonporous glass Raschig rings were taken as bed support that helps to remove generated gas from the system. The effect of variables such as column length-to-diameter ratio, catalyst cube dimension, and feed flow rate on the treatment of sewage water was studied. The reaction kinetics indicates that the nutrients uptake rate is dependent on both pore and film diffusion. The kinetics of uptake of nutrients follows a pseudo first-order reaction. From the pseudo reaction rate constant, Thiele modulus and effectiveness factor were calculated and a kinetic model equation for fractional nutrient uptake was developed in terms of operating variables. The model can predict the reaction rate with low deviation. The results obtained may be valuable for large-scale treatment of sewage water.